Penerapan Metode SAW Untuk Sistem Penunjang Keputusan Pemilihan Guru Terbaik Pada PKMI Binjai - Juliana; Tongam E Panggabean; Irwan Jani Tarigan (Jurnal Mahajana Informasi, 2022)
Giving awards to teachers is one of the strategies to increase work motivation and improve competence for teachers who have good performance. In Binjai Methodist High School in determining the best teacher, the attendance indicator is not fully sufficient to be used as a reference for awarding. Therefore, other criteria are needed that can be used as other additional criteria, therefore, it is necessary to develop a system that is capable of producing decision recommendations in determining the best teacher. In this study, the Simple Additive Weighting method (SAW) was used as a method which in its use included weighting/ratings on each criterion which would become a reference for teacher assessment. The criteria assessed in this study were educational level, teacher achievement/non-academic development, years of service, discipline, and examination/examination. From this study, the results were obtained that A1 = 0.98, A2 = 0.83, and A3 = 0.79 are 3 alternative decision recommendations from the best teacher who will be awarded.